Analysis of Tangent Hyperbolic over a Vertical Porous Sheet of Carreau Fluid and Heat Transfer - Ismael, Hajar F.; Hafidzuddin, Mohd Ezad Hafidz; Murad, Muhammad Amin S.; Arifin, Norihan Md; Bulut, Hasan (Semarak Ilmu Publishing, 2023)
The purpose of this study is to investigate the boundary layer of Carreau fluid and heat transfer over an exponentially stretching plate derived in a vertical porous with variable surface thermal flux. The partial differential equations that represent the momentum equation and heat equation are commuted into nonlinear ODEs by applying similarity transformations and results found numerically. The impact of several emerging dimensionless parameters labelled the Weissenberg number (We), the power-law index (n), Velocity slip (Sf), Thermal jump (St), and Prandtl number (Pr) on the velocity profile and heat transfer on the boundary layer are showed in detail. In more detail, also the influence of physical parameters on local skin friction and Sherwood number are studied. The shooting method with the explicit technique is used to find the solution and all results are illustrated graphically and numerically. We noted that by increasing power index, radiation parameter and velocity slip, the velocity profile increases, and the temperature profile decreases. Furthermore, it is deduced that rising the thermal radiation parameter reduces the local Nusselt number. © 2023, Semarak Ilmu Publishing. All rights reserved.
Keywords: Carreau Fluid; heat transfer; laminar flow; magnetic field; power index